The Ozone: Protecting the Oral Environment (Bangladesh Journal of Dental Research & Education, 2013)
Oxygen/ozone therapy is a term that describes a number of different practices in which oxygen, ozone, or hydrogen peroxide are administered via gas or water to kill disease microorganisms, improve cellular function, and promote the healing of damaged tissues. Ozone gas is immunostimulating, potent analgesic, detoxicating, antimicrobial, bioenergetics and biosynthetic properties as it causes activation of the metabolism of carbohydrates, proteins and lipids. The use of ozone has been advocated in Medical and Dental science due to its excellent antimicrobial, disinfectant and effervescent properties. The purpose of this article is to review the therapeutic applications of ozonated products in dentistry.DOI: http://doi.dx.org/10.3329/bjdre.v2i2.16246 Bangladesh Journal of Dental Research & Education Vol.2(2) 2012: 58-61